Optimasi Proses Bisnis Akuntansi Melalui Tahapan System Development Lifecycle Yang Efisien - O.Feriyanto; Riska Saumira Amanda; Citra Rahayu; Lusiana Lusiana; Okeu Kusmayanti; Shalma Ayu Miranda P (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2024)
This research focuses on optimizing accounting business processes through efficient stages of the System Development Lifecycle (SDLC). SDLC is a framework used to plan, develop, test, and maintain accounting information systems. In this study, each stage of the SDLC is analyzed to identify steps that can enhance the efficiency and effectiveness of accounting systems. The research method used is SDLC with a Waterfall approach, involving the stages of planning, analysis, design, implementation, testing, and maintenance. The results show that applying a structured SDLC can help companies manage accounting data more effectively, increase accuracy, reduce errors, and speed up accounting processes. This optimization also includes selecting the appropriate SDLC model, such as Waterfall and Prototype, based on the specific needs of the project and business environment. Thus, this research is expected to provide practical guidance for companies in optimizing their accounting business processes.